Cluster-Tic Syndrome secondary to neurovascular compression, a case report. - Neri, Pedro; Carvalho, Pedro Rubens Araujo; Alcantara, Raimundo Neudson Maia; França, Mario Hermes Rios; Junior, Luiz Gonzaga Nogueira; Queiroga, Morgana Feitosa de; Parente, Enzo Lima Alcântara; Rafaella Iughetti da Costa; Nogueira, João Vítor Moreira; Carvalho, Renata de Oliveira (Headache Medicine, 2024)
Introduction: When the association between cluster headache and trigeminal neuralgia happens it can be characterized as Cluster-Tic Syndrome, however, its presentation is heterogeneous and one of the conditions stands out. Objective: Discourse about the long journey of a patient until the Cluster-Tic Syndrome diagnosis. Case report: 58-year-old patient, over the last 10 years, refers to daily and intense/ shocking headaches, which last 30 minutes, in the left V2 territory and radiate to the ipsilateral superior lip and eye. The patient reports to have sought dental treatment and went through tooth extractions and laser therapy without any response. She was referred to the neurologist because of the more intense and frequent pain, which became disabling, associated with ipsilateral symptoms such as conjunctival hyperemia, tearing, rhinorrhea, periorbital edema and ptosis. During the consultation, the Headache Impact Test (HIT-6) was applied and evidenced severe impact (73 points). Due to the pain, the patient used many prophylactic (carbamazepine, lamotrigine, pregabalin) and abortive (NSAIDs, O2 and corticosteroids) medications without adequate response in preventing or treating the pain. The patient went through a brain MRI which evidenced contact of a vascular loop with the ipsilateral trigeminal nerve. Therefore, the patient was diagnosed with Cluster-Tic, having the cluster headache as the main entity and directing the treatment with verapamil. The patient was referred to neurosurgery to evaluate the necessity of surgical intervention. Conclusion: Cluster-Tic Syndrome is an extremely disabling condition due to the pain intensity and its difficult diagnosis and control, which leads to many years of low quality of life.